The Diet Problem of Food Menu for Starbucks in Malaysia: Linear Programming Problem - Abdul Rahim Khairul Anuar; Nurul Farihan Mohamed; Khalidah Irdina Khalid (Semarak Ilmu Publishing, 2024)
Indexed by MyCite